Transferrin Receptor 2 in Canine Testicular Tumors: An Emerging Key Role in Seminomas - Rebecca Leandri; Sara Buonocore; Karen Power (Animals)
Transferrin Receptor 2 (TfR2) is a homolog of Transferrin Receptor 1 (TfR1), involved in regulating intra and extracellular iron levels. Altered iron pathways have been associated with cancer onset and progression; however, their role in canine tumors remains poorly explored. This study investigated TfR2 immunohistochemical expression in non-neoplastic canine testis for the first time and in the most common types of canine testicular tumors: intratubular seminomas (ITSEMs), diffuse seminomas (DSEMs), Leydig cell tumors (LCTs), and Sertoli cell tumors (SCTs). Immunohistochemical analysis revealed a differential pattern of TfR2 expression according to tumor type, with high expression observed in ITSEMs and DSEMs, occasional expression in LCTs, and absence in SCTs. These results suggest that TfR2 may play a relevant role in canine seminoma development. Furthermore, the specific expression of TfR2 in seminomas highlights its potential as a therapeutic target, where its role in iron regulation and possible compensatory mechanisms warrant further investigation.